Textile and domestic effluent treatment via co-cultivation of Diplosphaera mucosa VSPA and Scenedesmus obliquus - Singh V.; Mishra A.; Srivastava P. (My University, 2025)
The present research aimed to study the efficiency of two microalgae strains in treating textile and domestic effluent in co-cultivation mode. A newly isolated strain, Diplosphaera mucosa VSPA, and Scenedesmus obliquus were co-cultivated in the mixotrophic and heterotrophic modes in the effluents. Monoculture cultivation mode acted as a control. Co-cultivation was performed at an inoculation ratio of 01:04 (Diplosphaera:Scenedesmus) in a conventionally designed 10 L photobioreactor. The highest biomass concentration was achieved in mixotrophic co-cultivation mode, which was 8.87 ± 0.05 g/L in domestic effluent and 6.14 ± 0.03 g/L in textile effluent. Biomass productivity in co-cultivation mode was nearly 1.5–2 times higher than in mono-cultivation mode. The substrate removal efficiency was also higher in the mixotrophic co-cultivation mode. More than 90% of ammonium-nitrogen, chemical oxygen demand, and 80% of phosphate-phosphorus removal were obtained from both effluents. Microscopic and flow cytometry analysis revealed that the final biomass concentration contains more Diplosphaera culture. It was concluded that the co-cultivation strategy is better than mono-cultivation for treating high-strength industrial effluent. Also, the experimental results of the co-cultivation mode were verified and simulated via various growth and substrate removal models. © 2023 Elsevier Ltd